Kinetic analysis of agility ladders drills and their comparison to sport-specific movements such as shuffling and sprinting - Scoles, B. S.; Sullivan, M.; Gold, M. E.; Blankenship, M. J.; Frisk, H. L.; Biggs, B. R. (ISBS Proceedings Archive (Michigan), 2023)
This study assessed agility ladder drills for the purpose of comparing kinetic characteristics of these drills to one another, and to sprinting and shuffling. Subjects (N=30) performed six agility ladder drills as well as sprinted and shuffled to the left and right over two large force platforms. A repeated measure ANOVA was used to assess horizontal and vertical ground reaction force (GRF) and the ratio of horizontal to vertical GRF, averaged from three steps for each drill. Significant main effects were found for all variables (p = 0.001). Post-hoc analysis identified differences (p = 0.05) between the agility drills as well as between the agility drills and the sprinting and shuffling. Results can be used to guide the progression of agility ladder drills based on known intensity and allow practitioners to prioritize drills that are most similar to sport-specific movements such as sprinting and shuffling